Mechanism towards free, fair and credible election in Africa : challenges to electorates and other actors of the electoral process - Muritala Dauda; Mohammad Zaki Ahmad; Mohammad Faisol Keling (Penerbit Universiti Kebangsaan Malaysia, 2019)
Election as a selection process for those that will represent the interest of the masses, need to be free, fair and credible. For an election to be credible, free and fair in which its result would be accepted by all, actors/stakeholders of the electoral process need to vigorously discharge their respective duties and obligation in the exercise. Evidence from the previous researches proved that Africa is having issues to conduct credible election. This study discovers that for Africa to have a credible election, players involved in the electoral process (such as the electoral bodies, the civil society, the judiciary, political parties, the mass media, and even the masses who are the electorates) are to be adequately cultured, orientated and given awareness on the beauty in discharging their role towards selection process of their leaders. Despitethe fact that, the voting behaviour of masses during an election tell more about the success of the system, but the actors or stakeholders involved in the electoral process can influence the level of voters’ turnout in an election, by given the electorates regular orientation and awareness on the electoral system in the society. The study makes use of Morality-Implicit Theory to explain how the electoral process can be free and fair, if the actors involved in the process imbibed moral value and transparency in discharging their duties to the system without fear or favour. This study therefore is a qualitative in nature that employs the use of secondary source of data to explain the mechanism towards free, fair and credible election in Africa.